The Role of Village Head Communication in Improving the Performance of State Civil Apparatus at the Gunung Kelua Village Office, Samarinda Ulu District, Samarinda City - Trisna Waty Riza Eryani; Ahmad Yani; Aji Syarif Hidayatullah; Nurhasanah (Asian Journal of Applied Business and Management, 2023)
Good government performance greatly influences public satisfaction, timeliness of service is one indicator that determines the good and bad performance of the State Civil Apparatus (ASN). This research aims to determine the role of the Head of Village communication in improving the performance of the State Civil Apparatus, as well as what factors influence the role of the Head of the Village in improving the performance of the State Civil Apparatus. The theory used is Effendy's communication theory, a type of qualitative descriptive research. The results of the research show that the role of village head communication in improving the performance of state civil servants at the Gunung Kelua sub-district office, Samarinda Ulu sub-district, Samarinda City is quite good.